Acid-catalyzed benzoylation reactions of Diels-Alder polyphenylenes. (5th December 2018) - Fujimoto, Cy; Sorte, Eric; Bell, Nelson; Poirier, Cassandria; Park, Eun Joo; Maurya, Sandip; Lee, Kwan-Soo; Kim, Yu Seung
Abstract: Post-polymerization reactions of Diels-Alder polyphenylene with ring-substituted benzoyl chloride derivatives using triflic acid as the catalyst, effected selective Friedel-Crafts acylation of the lateral phenyl groups attached to the polyphenylene backbone. Using 4-(trifluoromethyl) benzoyl chloride gave a polymer with increased hydrophobicity. Using 4-fluorobenzoyl chloride afforded lateral 4-(fluorobenzoyl)phenyl substituents, which were further functionalized by nucleophilic aromatic substitution of the reactive fluoro substituent by 4-methoxyphenol. Graphical abstract: A general approach of attaching benzoyl groups on to Diels-Alder poly(phenylene) [DAPP] is discussed. Triflic acid has been found to be an excellent catalyst for Friedel-Crafts benzoylation attachment of 4-(trifluoromethane)benzoyl chloride and 4-fluorobenzoyl chloride to DAPP with high efficiencies. Triflic acid-catalyzed Friedel-Crafts benzoylation offers a simple route to post-functionalize DAPP with a variety of benzoyl units. Highlights: Post functionalization of Diels-Alder polyphenylene with fluorine containing benzoyl chloride derivatives. Attachment of nearly six trifluoromethylbenzoyl groups onto the poly(phenylene) backbone increases hydrophobicity. Attachment of 4-fluorobenzoyl groups onto the poly(phenylene) backbone allows for subsequent functionalization.